THE COMPARISON OF SEISMIC SECTION BETWEEN PHYSICAL MODELLING AND NUMERICAL ISOTROPIC MODELLING IN ANISOTROPIC MEDIA - SULAKSANA (NIM 22305002); Pembimbing: Dr. Eng. TA Sanny dan Dr.rer.nat. R.M Rachmat Sule, RAMDHAN
Geophysicists face a difficult challange to find new oil and gas reserves, both in the mature area and in brown and marginal fields. Therefore, they need a reliable seismics technology in order to map the new reserves well. In addition, the ability of a geophysicist should be increased because the new reserves usually find in a condition which is geologically complex. The research's purpose is to test a capability of sismics method in mapping a complex and shallow structure of under surface geology, where the possibility of micro oil and gas reservoar could be found. This research applies physical and numerical modelling to solve the equation of elastic wave. This is a basic for modelling an elastic wave propagation. The equation of elastic wave being solved by using finite difference method. The solution for numerical modelling is a snapshot of wave front contrast toward the time. Besides snapshot, there is also synthetics seismogram that is by product of seismics wave modelling. The model in this research based on physical modelling that are anticlin and sinclin model, with assumption the isotropy medium upper layer. That model are used as an input program for numerically elastic propagation wave simulation. The results of numerical modelling compared to the results of physical modelling. The image of anticlin showed clearly both in numerical and physical modelling. Meanwhile, the image of siclin showed blur in physical modelling if it was compared to the result of numerical modelling. The image of siclin and anticlin in numerical modelling showed clearly in the results of snapshot simulation, which showed the changes of seismics wave front toward the time when the seismic wave energy run through anticlin and siclin structure. The results of raytracing illustrate the rays that run trough the model showed the changes of rays direction when rays runs through anticlin and siclin area. To make the image of siclin structure shows clearer in physical modelling, therefore the next research the value of velocity and density from the siclin and the medium sorround it need to be changed.